The Gaia-ESO Survey: double-, triple-, and quadruple-line spectroscopic binary candidates - Merle, T.; van Eck, S.; Jorissen, A.; van der Swaelmen, M.; Masseron, T.; Zwitter, T.; Hatzidimitriou, D.; Klutsch, A.; Pourbaix, D.; Blomme, R.; Worley, C. C.; Sacco, G.; et al. (2017)
Context. The Gaia-ESO Survey (GES) is a large spectroscopic survey that provides a unique opportunity to study the distribution of spectroscopic multiple systems among different populations of the Galaxy. Aims: Our aim is to detect binarity/multiplicity for stars targeted by the GES from the analysis of the cross-correlation functions (CCFs) of the GES spectra with spectral templates. Methods: We developed a method based on the computation of the CCF successive derivatives to detect multiple peaks and determine their radial velocities, even when the peaks are strongly blended. The parameters of the detection of extrema (DOE) code have been optimized for each GES GIRAFFE and UVES setup to maximize detection. The DOE code therefore allows to automatically detect multiple line spectroscopic binaries (SBn, n ≥ 2). Results: We apply this method on the fourth GES internal data release and detect 354 SBn candidates (342 SB2, 11 SB3, and even one SB4), including only nine SBs known in the literature. This implies that about 98% of these SBn candidates are new because of their faint visual magnitude that can reach V = 19. Visual inspection of the SBn candidate spectra reveals that the most probable candidates have indeed a composite spectrum. Among the SB2 candidates, an orbital solution could be computed for two previously unknown binaries: CNAME 06404608+0949173 (known as V642 Mon) in NGC 2264 and CNAME 19013257-0027338 in Berkeley 81 (Be 81). A detailed analysis of the unique SB4 (four peaks in the CCF) reveals that CNAME 08414659-5303449 (HD 74438) in the open cluster IC 2391 is a physically bound stellar quadruple system. The SB candidates belonging to stellar clusters are reviewed in detail to discard false detections. We suggest that atmospheric parameters should not be used for these system components; SB-specific pipelines should be used instead. Conclusions: Our implementation of an automatic detection of spectroscopic binaries within the GES has allowed the efficient discovery of many new multiple systems. With the detection of the SB1 candidates that will be the subject of a forthcoming paper, the study of the statistical and physical properties of the spectroscopic multiple systems will soon be possible for the entire GES sample. Based on data products from observations made with ESO Telescopes at the La Silla Paranal Observatory under programme ID 188.B-3002. These data products have been processed by the Cambridge Astronomy Survey Unit (CASU) at the Institute of Astronomy, University of Cambridge, and by the FLAMES/UVES reduction team at INAF/Osservatorio Astrofisico di Arcetri. These data have been obtained from the Gaia-ESO Survey Data Archive, prepared and hosted by the Wide Field Astronomy Unit, Institute for Astronomy, University of Edinburgh, which is funded by the UK Science and Technology Facilities Council.
Keywords: Astrophysics - Solar and Stellar Astrophysics; binaries: spectroscopic; globular clusters: general; methods: data analysis; open clusters and associations: general; techniques: radial velocities